A combined modelling and experimental study of heat shock factor SUMOylation in response to heat shock. (7th December 2021) - Zhang, Manyu; Zhao, Alice; Guo, Chun; Guo, Lingzhong
Highlights: A dynamical model is developed to study the role of HSF1 SUMOylation in response to heat shock. An experiment is conducted for the purpose of validation of the proposed model in terms of the SUMOylation levels under the heat shock. An experiment is conducted to verify the developed model. Our results show that the SUMOylated HSF1 levels agree closely with the experimental findings. Abstract: One of the most important questions in cell biology is how cell fate is determined when exposed to extreme stresses such as heat shock. It has been long understood that organisms exposed to high temperature stresses typically protect themselves with a heat shock response (HSR), where accumulation of denatured or unfolded proteins triggers the synthesis of heat shock proteins (HSPs) through the heat shock transcription factor, e.g., heat shock factor 1 (HSF1). In this study, a dynamical model validated with experiments is presented to analyse the role of HSF1 SUMOylation in response to heat shock. Key features of this model are inclusion of heat shock response and SUMOylation of HSF1, and HSP synthesis at molecular level, describing the dynamical evolution of the key variables involved in the regulation of HSPs. The model has been employed to predict the SUMOylation levels of HSF1 with different external temperature stimuli. The results show that the SUMOylated HSF1 levels agree closely with the experimental findings. This demonstrates the validity of this nonlinear dynamic model for the important role of SUMOylation in response to heat shock.